Paradoxical normativities in Brunei Darussalam and Malaysia: Islamic law and the ASEAN Human Rights Declaration - Mueller, Dominik M. (Asian Survey, 2016)
Brunei and Malaysia are promoting the ASEAN Human Rights Declaration but enforce a brand of Islamic law that systematically violates it. The paradoxical ways in which policymakers are navigating between the two, and the empirical realities of Islamic governance, impede the project of a transdoctrinal justification of human rights.
Created from Fastlane, Scopus look-up
Keywords: ASEAN; Brunei darussalam; Human Rights; Islamic governance; Malaysia